Short-Term Results of HATCP Coated Femoral Head Prosthetic Replacement - Kashiwagi, Teruyuki; Sonoda, Norio; Chosa, Etsuo; Toda, Masashi; Tajima, Naoya; Fukanoki, Yuki (Orthopedics & Traumatology, 1997)
This paper evaluated the utility of HATCP coated femoral head prostetic replacement. This prosthesis has been used in 24 cases of femoral neck fracture and 2 cases with necrosis of the femoral head since 1995 in our department. All patients started partial weight bearing from 1 week postoperatively. Short-term follow-up (mean: 1 year 2 months) was carried out. Subjects included 24 cases 7 male and 17 female ranging from 51 years to 89 years (mean: 80). The averege postoperative JOA hip score was 83 points. No patients developed thigh pain, limping gait or the Trendelenburg sign. Regarding the radiological results, there were radiolucent lines around the prosthesis in 4 cases. However no radiolucent line was found around the HATCP coated stem and sinking did not appear. The short-term clinical results were good and we found osteoconduction in 72% of patients around the HATCP coated stem 6 months after surgery.